2018
DOI: 10.3390/en11113121
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Flow Maldistribution in Multi-Plate Heat Exchangers Based on Robust 2D Model

Abstract: Plate heat exchangers (PHE) are characterized by high heat transfer efficiency and compactness. An exploitation problem of the PHE is related to flow maldistribution, which can make part of the PHE idle, resulting in overheating and damage. Making geometrical modifications to the PHE can help reduce flow maldistribution. Modifications should be kept to a minimum, so as not to complicate the production process. There is a large number of possible geometrical modifications, which simply considers additional obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In the currently developed numerical model the computational domain was divided into five separated regions as shown in Figure 5. This can be perceived as a simplified geometrical feature of a plate heat exchanger (PHE) [40,41], which usually consists of a large number of thin plates separated by a small gap. Consequently, the PHE channels contain alternately hot and cold fluid.…”
Section: Numerical Modelmentioning
confidence: 99%
“…In the currently developed numerical model the computational domain was divided into five separated regions as shown in Figure 5. This can be perceived as a simplified geometrical feature of a plate heat exchanger (PHE) [40,41], which usually consists of a large number of thin plates separated by a small gap. Consequently, the PHE channels contain alternately hot and cold fluid.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Flow maldistribution in the inlet header and its effects on the thermal performances were investigated using theoretical analysis, computational fluid dynamic (CFD) simulations, and experimental testing technologies in the past few decades [7,8]. Lalot [9] calculated the outlet velocity ratio to represent the flow maldistribution, and the results indicated that the gross flow maldistribution led to a loss of effectiveness of about 7% for counterflow heat exchangers and up to 25% for crossflow exchangers.…”
Section: Of 14mentioning
confidence: 99%
“…The adsorber design has to increase heat transfer while also decreasing intra-and interparticle mass transfer resistance [20]. Moreover, the flow maldistribution should be minimized [23]. According to [21], adsorption kinetics are strongly reduced in the case of excessive adsorbent thickness.…”
Section: Heat Exchangers: New Types Of Adsorption Bedsmentioning
confidence: 99%